A comparison of the precision of 3D images of facial tissues from the forensic point of view. (March 2022) - Eliasova, Hana; Dostalova, Tatjana; Urbanova, Petra
Highlights: Our contribution confirmed visual and metric correlation between 3D CBCT and facial scanner. Maxillofacial surgery had direct influence on shape and size of face. Residual accounted for a significant fraction of total variance ranging from 95 to 98.5 %. Pre/post-surgery facial differences were clearly visualized via color deviation maps. Abstract: Objective: The size and shape of the facial skeleton are fundamental determinants of the facial appearance. Small asymmetries in skeletal morphology are noticeable, but changes during forensic identification, orthodontic therapy, or maxillofacial surgical intervention are mostly much more powerful. Soft tissues can particularly eliminate deformities or accentuate them. Orthodontics and maxillofacial surgery use imaging techniques which can directly analyze soft and hard tissues. For that reason, those techniques can be generally used also in forensic anthropology and forensic dentistry settings. The aim of this study is to compare accuracy of 3D facial images acquired by the 3dMD facial scanner and the cone-beam CT unit. Material and methods: Our research group consisted of 32 patients who underwent a treatment plan for maxillofacial surgery, followed by orthognathic surgery. Pre- and post-operative 3D facial recordings acquired by the 3dMD facial scanner and cone-beam CT unit were analyzed and compared using the FIDENTIS Analyst Software and 3D Dolphin Imaging Software. The statistics were computed using Statistica 13 and PAST 3.0 packages. Results: The results indicate that maxillofacial surgery is a factor that increases significantly the within-sample variation. The acquisition technologies were seen as a minor agent, which, however, should be of concern if both, the point-based as well as the Iterative Closest Point (ICP) registration is to be employed. Conclusion: The 3D methods of surgery planning and therapy provided specific information not only about surgical treatment options, but also for 3D comparison procedures applicable in forensic dentistry and facial identification. Graphical Abstract: Image, graphical abstract